PENGEMBANGAN MEDIA BELAJAR INTERAKTIF LKPD BERBASIS LIVEWORKSHEET PADA MATA PELAJARAN PKN KELAS 6 SD - Nur Wahidah Yuliati; Sutrisna Wibawa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The research carried out focused on developing Liveworksheet-based E-LKPD learning media for class VI elementary school Civics lesson content, especially Rights and Obligations material. This research was carried out using the R&D development research method with the ADDIE model. In the ADDIE model there are five stages, namely Analyze, Design, Develop, Implement, and Evaluate. In this research, the researcher tried to reach the Evaluate stage because the researcher wanted to know to what extent this development was suitable for use based on the assessment of the validator. The results of validation of learning media by media experts and material experts obtained a score of 85% which is included in the Very Appropriate or Very Good category because the percentage of validation results is in the range 81-100%. Thus, Liveworksheet-based E-LKPD learning media for Civics lesson content is very suitable for use in the learning process. This Liveworksheet-based E-LKPD learning media can increase the use of technology, on the other hand it also makes students enthusiastic in participating in the learning process.